Desenvolvimento, caracterização e aplicação tecnológica de farinhas elaboradas com resíduos da produção de suco de uva - Natividade, Mariana Mirelle Pereira (2010)
In recent decades, several studies have demonstrated the positive health effects of consuming foods rich in phenolic compounds to health. In this sense, this study aims to evaluate the physicochemical and functional characteristics of three different grape juices integral: Isabel Precoce, Bordô and Blend. Still, it was intended to prepare and characterize flour produced from grape pomace. For both, employed two methods of dehydration: dried at 60 ± 5 °C and lyophilization. At the end of processing, we obtained six different flours. After preparation of the flours, was evaluated their microbiological standard, and then proceeded the application of these products in yogurt, in order to evaluate their sensory acceptance. About the legal parameters, some juice samples showed off the required standards for TSS and total sugars. It was found that most physical and chemical attributes of the juices was related to the characteristics of the varieties of grapes used in processing. The juices Bordô showed to be better in many aspects such as higher levels of phenolics, anthocyanins and higher antioxidant potential. The pomace grape and flour grape showed satisfactory microbiological quality, not occurring growth of coliforms, Salmonella sp. or Bacillus cereus. Therefore, the product developed is safe for human consumption from the health point of view. In flours grape, this result may have been caused by their intrinsic characteristics. For most of the physicochemical parameters evaluated, the method of dehydration and cultivate the grape juice exhibited significant influence. The flour grape dehydrated by lyophilization showed the best levels of vitamin C, phenolics, anthocyanins, antioxidant activity and color more attractive, thus demonstrating the efficiency of this method of dehydration in the preservation of bioactive compounds studied. The chemical composition of the flours grape, significant levels of dietary fiber were observed, which represented approximately 50% of product weight. The flours grape prepared with the residue of juice Bordô was the best in the functional aspects. However, the sensory evaluation of yogurt add the flour grape, indicated that Isabel Precoce lyophilized flour showed higher levels of acceptability and market potential. Thus, this study indicated that the utilization of the pomace processing of grape juice may be an important alternative insertion of bioactive compounds in food, besides being a strategy to reduce the environmental impact caused by the incorrect elimination of this material.